Marketing Strategy for MSME Financing Products at Islamic Banks in Indonesia in the Digital Era - Agus Rahayu; Aen Fariah; Saeful Anwar (Journal of Sharia Micro Enterprise and Cooperation, 2026)
Background: The development of the digital era has brought significant changes to marketing strategies in the Islamic banking industry, particularly in Micro, Small and Medium Enterprise (MSME) financing products, yet empirical research specifically examining these strategies remains scarce.Objectives: This study aims to analyze the digital marketing strategies applied by Islamic banks in Indonesia to promote MSME financing products, identify the challenges faced, and formulate effective strategy recommendations.Methods: A sequential explanatory mixed-methods design was employed, beginning with a qualitative phase in-depth interviews with 12 Islamic bank practitioners used to inform a subsequent quantitative phase comprising a survey of 150 MSME customers; secondary data were drawn from annual reports of Indonesian Islamic banks, Bank Indonesia regulations, and Financial Services Authority (OJK) data from 2020–2024.Results: Islamic banks in Indonesia have implemented four digital marketing strategies social media marketing, mobile banking-based financial technology, digital content marketing, and digital customer relationship management (CRM) while facing significant challenges including limited digital literacy among MSME players, high operational costs of digital transformation, and regulatory complexity an integrated digital marketing strategy combining conventional and digital approaches was associated with a 43% increase in MSME financing product penetration compared to conventional methods alone.Conclusion: These findings contribute to filling a research gap concerning digital marketing strategies specifically tailored to MSME financing products within the Islamic banking context in Indonesia and offer practical implications for banks and regulators seeking to strengthen digital financial inclusion.